2021
DOI: 10.1111/are.15460
|View full text |Cite
|
Sign up to set email alerts
|

Review: A bibliometric survey of live feed for marine finfish and shrimp larval production

Abstract: Aquaculture is one of the fastest developing food production sectors worldwide with an overall 5.8% of annual increase during the period from 2000 to 2016 (FAO, 2018). However, increasing the output of marine fish has proven difficult over the years as appropriate access to high quality live feed, for example, copepods is one of the primary bottlenecks in developing marine finfish production (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Previous studies showed that Biokos has no adverse effect on bacteria associated with water purification/nitrification at 12.6 mg/L. In another experiment, none of 12 gram‐negative bacterial species showed a minimal inhibitory concentration of less than 128 mg/L of Biokos (Hansen et al, 2022; J. Hansen, personal communication). We, therefore, believe there is a low risk of reducing the performance of biofilters in saltwater, but this remains to be tested.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies showed that Biokos has no adverse effect on bacteria associated with water purification/nitrification at 12.6 mg/L. In another experiment, none of 12 gram‐negative bacterial species showed a minimal inhibitory concentration of less than 128 mg/L of Biokos (Hansen et al, 2022; J. Hansen, personal communication). We, therefore, believe there is a low risk of reducing the performance of biofilters in saltwater, but this remains to be tested.…”
Section: Discussionmentioning
confidence: 94%
“…Using Biokos in land‐based aquaculture systems that use running sea water will require considering the impact of Biokos on the environment. A few studies have investigated the natural degradation of Biokos and similar molecules, finding that they degrade to their constituent amino acids and medium‐chain fatty acids in 2–5 days, including in saltwater (Hansen et al, 2022; Nielsen & Sørensen, 2003). These observations, together with results from testing Biokos for toxicity to a number of beneficial aquatic organisms (Korbut et al, 2022), indicate that the use of Biokos in land‐based aquaculture systems is feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artemia is produced in every continent except for Antarctica [ 42 , 43 , 44 , 45 , 46 , 47 ]. Moreover, previous studies have also shown some information about the bibliometric knowledge on live feed such as Artemia [ 47 ], but did not focus on a detailed explanation of the studies, in contrast to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Commercialization of the relevant research contributions are encouraged to be accomplished under collaborations between academia and industry (Hansen et al, 2017). Another important step is continuous meetings between academia and industry at international levels in relevant forums e.g., LARVI-conference and the European Aquaculture Society to further support the development of the marine aquaculture (Hansen and Møller, 2021).…”
Section: Perspectivationmentioning
confidence: 99%